Theoretical Studies on Structures and Electronic State of Alkyl-Substituted Ethyl Cations - Toshiaki Shimasaki; Ken Nakayasu; Mitsuhiro Shibata; Tatsuaki Yamaguchi (Journal of Chemistry)
This paper describes the gas phase structural details for a series of alkyl-substituted ethyl cations 1–11 by mainly natural bond orbital (NBO) analysis. For the simplest ethyl cation, two kinds of optimized structures (nonclassical 1 and classical 2) were found to have minima on the potential surface, and the nonclassical 1 was more stable than the corresponding classical 2 by 1.19 kcal/moL at Møller-Plesset (MP) level calculations in the gas phase. The calculated values of Wiberg’s bond index revealed that the central ethylic C1–C2 bonds of the nonclassical cations 1, 6, 7, and 10 have 1.10–1.46 bond multiplicities. The compliance constant () values indicated that the cation center C1 of nonclassical 2-butyl cation 6 (0.209 Å/mdyn) acquires stronger hyperconjugative stabilization from C2–R3 (C–H) bond than that of the nonclassical ethyl cation 1 (0.388 Å/mdyn). Moreover, the gas phase stabilities for the alkyl-substituted ethyl cations 1–11 were also estimated by the hydride affinities based on isodesmic equations.